2008
DOI: 10.3846/1392-8619.2008.14.531-545
|View full text |Cite
|
Sign up to set email alerts
|

Experience of the Game Theory Application in Construction Management / Lošimų Teorijos Taikymo Patirtis Statybos Vadyboje

Abstract: Abstract. The game theory allows mathematical solutions of conflict situations. Besides the fairly established application to economical problems, approaches to problems in construction operation have been worked out. An overview of applications is given. Solution strategies for such engineering problems are collected. Furthermore, concrete application examples are presented and an overview of further potential applications is given. Solutions of two-person zero-sum games are discussed as well as approaches to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 12 publications
0
33
0
Order By: Relevance
“…There is a wide range of methods ( (Zavadskas and Kaklauskas 1996); Game theory methods (Zavadskas and Turskis 2008;Peldschus 2008Peldschus , 2009Ginevičius and Krivka 2008;Turskis et al 2009) and other methods (Turskis 2008).…”
Section: Madm Methods For Solving the Problemmentioning
confidence: 99%
“…There is a wide range of methods ( (Zavadskas and Kaklauskas 1996); Game theory methods (Zavadskas and Turskis 2008;Peldschus 2008Peldschus , 2009Ginevičius and Krivka 2008;Turskis et al 2009) and other methods (Turskis 2008).…”
Section: Madm Methods For Solving the Problemmentioning
confidence: 99%
“…In Antuchevičienė 2006, 2007) the authors analyse modelling renewal of construction objects applying the methods of the Game Theory (Peldschus 2008). The authors present selecting of rational renewal variants of derelict buildings from the viewpoint of sustainable development.…”
Section: Related Work On Attributes For the Assessment Of Dwelling Hmentioning
confidence: 99%
“…While studying negotiations, the game theory deals with a number of games; here, the games are often classifi ed as zero-sum games, in which a gain of one individual means loss for another, and non-zero-sum games, in which all players may win on a basis of individual decisions, as well as cooperative games when coalitions are possible and non-cooperative games which follow the rule of antipathy (Pearce, 2006). Zavadskas et al (2004), Peldschus (2005Peldschus ( , 2009, Meszek (2008) and Turskis et al (2009) analysed possibilities to apply the game theory methods in tasks related to construction technology and management, and demonstrated that typical tasks of construction technology and management correspond to zero-sum games of two persons. Zavadskas et al (2008a) applied multi-criteria selection of contractor in a competitive environment using the game theory.…”
Section: Game Theory Economic Theory Multiple Criteria Decision Anamentioning
confidence: 99%